2022
DOI: 10.3390/su14159414
|View full text |Cite
|
Sign up to set email alerts
|

Development of Eco-Friendly Cutting Fluid for Machining of AISI 1010 Steel in Automotive Industry

Abstract: In spite of better performance, the disposal of used petroleum-based cutting fluids threatens our environment. Thus, it is essential to develop eco-friendly cutting fluids for performing machining operations in industries. The main contribution of this paper is to develop an eco-friendly cutting fluid for the plain turning of AISI 1010 steel which is used in the automotive industry. In the present work, boric acid (H3BO3) was mixed with the neem seed. Neem seed oil is easily available in many countries includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 36 publications
0
0
0
Order By: Relevance
“…Another study from Marichelvam et al, investigated the use of soybean oil-based cutting fluid with an environmentally friendly additive for machining of aluminum alloys. The study found that the soybean oil-based fluid with the additive provided better cooling and lubrication compared to conventional mineral oil-based fluids, resulting in improved surface finish and reduced tool wear [4].…”
Section: Introductionmentioning
confidence: 99%
“…Another study from Marichelvam et al, investigated the use of soybean oil-based cutting fluid with an environmentally friendly additive for machining of aluminum alloys. The study found that the soybean oil-based fluid with the additive provided better cooling and lubrication compared to conventional mineral oil-based fluids, resulting in improved surface finish and reduced tool wear [4].…”
Section: Introductionmentioning
confidence: 99%